Managing Operational Risks with ERM to Boost Tea Supply Chain Productivity - Ayi Tejaningrum (AIBPM Publisher, 2026)
Operational risk analysis in the plantation industry remains underexplored, despite its exposure to weather uncertainty and perishable commodities. This study stands out by employing grounded research to identify supply chain risk variables and focus group discussions (FGDs) to develop risk management solutions. It aims to boost tea productivity at Plantation Company (PT XYZ), a state-owned enterprise in West Java, Indonesia, by examining risks across plantations, processing, and distribution. The research addresses low tea yields in plantations, which reduce factory output and fail to meet consumer expectations. Using a survey-based approach with Enterprise Risk Management (ERM) tools, risk variables were derived from grounded research, and a questionnaire assessed risk probabilities and impacts. Involving 70 respondents, the study used FGDs to finalize risk scores and propose mitigation strategies. The findings identify 39 risks: 16 upstream, 12 internal supply, and 11 downstream. Key risks affecting tea production include human resource challenges, such as work accidents, fatigue, and demotivation from repetitive tasks, alongside fertilizer shortages, fraud risks, and high distribution costs. Effective risk mitigation requires government support for price stability, fertilizer supply, and fuel subsidies, along with strong leadership, continuous risk analysis, and operational monitoring.